DESIGN AND IN VIVO EVALUATION OF NAPROXEN-LOADED TRANSFEROSOMAL GEL FOR TRANSDERMAL DELIVERY - BINDU E., HIMA; G. V., RADHA (International Journal of Applied Pharmaceutics, 2024)
Objective: The main objective of the present study was to formulate, optimize, and evaluate naproxen transfersomal gels. Methods: Reverse phase evaporation was used to create thirteen different formulations of naproxen-loaded transfersomes. Using Response Surface Methodology (RSM) and Central Composite Designs (CCD), the influence of independent process variables, such as soy lecithin, cholesterol content and surfactant concentration, on dependent variables, such as entrapment effectiveness and vesicle size of naproxen transfersomes, was assessed. In vitro, ex-vivo, and in vivo drug release of formulations were also studied. Results: It was discovered that the NTG7 formulation of transfersomes had the maximum entrapment effectiveness and ideal vesicle diameter. The optimized NTG7 formulation displayed a maximum drug content of 97.4% and a maximum drug release of 88.03%. The release of naproxen from the final gel adhered to the Korsmeyer-Peppas release model. The ex-vivo drug release of the optimized formulation was found to be 85.91% for 24 h. The maximum drug concentration after oral administration was 843.54±7.67ng/ml, and Tmax was 3.0±0.08h. The improved formulation's AUC0-∞ was greater than the commercial formulation's. A higher drug concentration in the blood compared to the marketed formulation suggested better systemic absorption of naproxen from the gel formulation. After three months, at a temperature range of 2 to 8 °C, the formulation demonstrated correct semisolid consistency and good stability and there was also no appreciable change in the initial values of appearance, pH, and % drug content. Conclusion: The above findings imply that the gel created using naproxen-loaded transfersomes may be a potentially valuable new formulation.